Retrospective Study on the Incidence of Type 2 Diabetes Mellitus in Industrial Workers in Sharjah Industrial Area Aged 45-60 with Shift Work and Irregular Sleep Patterns - Osaid, Muhammad (Indus Journal of Bioscience Research, 2025)
This retrospective cohort study investigated the relationship between shift work, sleep patterns, and the incidence of Type 2 Diabetes Mellitus (T2DM) among 324 industrial workers aged 45–60 years in the Sharjah Industrial Area, United Arab Emirates. Data spanning two years (April 2022–March 2024) were extracted from electronic medical records and occupational health files. The findings revealed a high incidence of T2DM (26%) among workers with irregular sleep patterns, exceeding the 18% prevalence rate reported in the general expatriate population of similar age. Notably, a dose-response relationship was observed, with diabetes incidence rising by 7.5% for every additional five years of shift work. Workers exposed to shift schedules for over ten years showed diabetes rates above 30%, while nearly one-third (29.5%) of the population was classified as pre-diabetic. Multivariable logistic regression identified irregular sleep duration (<6 hours) as an independent predictor of diabetes (OR = 2.6; 95% CI: 1.8–3.7, p < 0.01), and prolonged shift work exposure (>5 years) significantly increased diabetes risk (OR = 3.1; 95% CI: 2.0–4.5, p < 0.001), regardless of BMI, age, or sex. The highest BMI recorded in the study was 35.4 kg/m², and the peak HbA1c level observed was 9.2%. These findings underscore the significant occupational health burden of shift work and sleep disruption, emphasizing the urgent need for targeted interventions such as structured sleep hygiene programs, optimized shift scheduling, and regular metabolic screenings in industrial populations.